Jeremy Bentham on David Hume: “Having Enter’d into Metaphysics,” but “Having Lost His Way” - Zhang Yanxiang (Open Philosophy, 2023)
This article argues that Bentham’s metaphysics has until recently been unfairly belittled, and that it in fact built on and surpassed that of David Hume, of whom Bentham was both an attentive student and a fierce critic. Bentham’s logic is metaphysically based, multi-levelled, and comprehensive. First, taking Hume’s empiricism as a starting point, Bentham developed the additional mechanism of “reflection” to facilitate a utilitarian pragmatic resolution to Hume’s skepticism. Second, unlike Hume, Bentham aspired to encyclopedic knowledge, especially of the human mind, which he believed allowed him to place his thought on a more solid and broader foundation. Third, whereas Hume focused on the passive understanding, Bentham captured the interaction between understanding and volition. Fourth, in relation to moral approbation, Hume adopted an approach which highlighted benevolence, whereas Bentham sought to reconcile self-preference with benevolence. Fifth, Hume’s common sense moral philosophy pushed him to associate justice with social convention, and helped to make him a conservative. Bentham developed the principle of utility to direct and push forward social reform for a better world.